Pengelolaan Sumber Belajar Berbasis Digital dalam Meningkatkan Kualitas Proses Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 36 Kota Bengkulu - Sari Wulandari; Jepi Elia Sari (Al-Khair Journal: Management Education, 2026)
Abstract: The purpose of this study is to analyze the management of digital-based learning resources in improving the quality of the Islamic Religious Education learning process at State Elementary School 36, Bengkulu City. Using descriptive qualitative methods. The research subjects were the Principal, Vice Principal, Islamic Religious Education teachers, Administrative Staff and students. Data collection techniques include observation, interviews, and documentation. Data analysis techniques use the theory of Miles and Huberman with the following steps: (1) data reduction, (2) data presentation, (3) drawing conclusions and verification. To maintain data validity, a validity test was carried out using source and method triangulation techniques. The results of the study indicate that the management of digital-based learning resources at SDN 36, Bengkulu City has been implemented through structured planning, implementation, and evaluation, although there are still limitations in optimizing its use. Good management of digital learning resources has been proven to contribute to improving the quality of the Islamic Religious Education learning process to be more interactive, varied, and meaningful for students. Thus, it can be concluded that the management of digital-based learning resources can improve the quality of the Islamic Religious Education learning process in schools. So it can be suggested to improve the quality of the learning process, then improve the management of digital-based learning resources in schools.Keywords: Digital-Based Learning Resource Management, Quality of Learning Process, Islamic Religious Education, Elementary School.  Abstrak: Tujuan penelitian ini untuk menganalisis pengelolaan sumber belajar berbasis digital dalam meningkatkan kualitas proses pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 36 Kota Bengkulu. Menggunakan metode kualitatif deskriptif. Subjek penelitian Kepala Sekolah, Wakil Kepala Sekolah, guru Pendidikan Agama Islam, Staf Tata Usaha dan siswa. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan teori Miles dan Huberman dengan langkah-langkah: (1) reduksi data, (2) penyajian data, (3) penarikan kesimpulan dan verifikasi. Untuk menjaga validitas data dilakukan uji keabsahan dengan teknik triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa pengelolaan sumber belajar berbasis digital di SDN 36 Kota Bengkulu telah dilaksanakan melalui perencanaan, pelaksanaan, dan evaluasi yang terstruktur, meskipun masih terdapat keterbatasan dalam optimalisasi pemanfaatannya. Pengelolaan sumber belajar digital yang baik terbukti berkontribusi dalam meningkatkan kualitas proses pembelajaran PAI menjadi lebih interaktif, variatif, dan bermakna bagi siswa. Dengan demikian dapat disimpulkan bahwa pengelolaan sumber belajar berbasis digital dapat meningkatkan kualitas proses pembelajaran pendidikan Agama Islam di sekolah. Sehingga dapat disarankan untuk meningkatkan kualitas proses pembelajaran, maka tigkatkanlah pengelolaan sumber belajar berbasis digital di sekolah.Kata kunci: Pengelolaan Sumber Belajar Berbasis Digital, Kualitas Proses Pembelajaran, Pendidikan Agama Islam, Sekolah Dasar.